Current sensorless vector controlled induction motor drive - Vimlesh Verma (Institute of Advanced Engineering and Science, 2019)
This paper presents a current sensorless vector controlled induction motor drive with only speed sensor present in the system. The same performance as that of normal vector control drives (which uses two current and one speed sensor) is achieved with the proposed current sensorless drive. Such an approach is suitable for applications, where speed sensor cannot be eliminated. Thus, elimination of current sensor results in reduction of cost, increases reliability, reduced size and noise immunity. A new current estimation algorithm is proposed in this paper. The current estimation algorithm, estimates the current in two phase stationary reference frame. The proposed current estimation technique can also be used as a fault tolerant algorithm for normal vector controlled drives in case of current sensor failures. The performance of the current sensorless drive using the proposed current estimation technique is verified through MATLAB/SIMULINK. Extensive simulation results are presented to confirm the effectiveness of the algorithm. The algorithm is also experimentally validated with the laboratory developed prototype and the results are presented. The prototype is built around a dSPACE 1104 controller board.